2016
DOI: 10.1111/1744-7917.12375
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis in the beet webworm, Spoladea recurvalis (Lepidoptera: Crambidae)

Abstract: The beet webworm, Spoladea recurvalis Fabricius, is a destructive pest on vegetable crops in tropics and subtropics; its main host plant is amaranth. It has become imperative to develop non-chemical methods to control S. recurvalis on amaranth. However, the lack of molecular information about this species has hindered the development of novel pest management strategies. In this study, high-throughput RNA sequencing covering de novo sequence assemblies, functional annotation of transcripts, gene function classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…We used PICRUSt software for analysis. The COG database mainly contains information about bacteria and archaea genomes (Chang and Ramasamy, 2018). In CCl 4 -induced liver fibrosis mice, the enriched COG terms are as follows: "Secondary metabolites biosynthesis, transport and catabolism, " "Cytoskeleton, " and "Intracellular trafficking, secretion, and vesicular transport."…”
Section: Prediction Of the Function Of Microbiotamentioning
confidence: 99%
“…We used PICRUSt software for analysis. The COG database mainly contains information about bacteria and archaea genomes (Chang and Ramasamy, 2018). In CCl 4 -induced liver fibrosis mice, the enriched COG terms are as follows: "Secondary metabolites biosynthesis, transport and catabolism, " "Cytoskeleton, " and "Intracellular trafficking, secretion, and vesicular transport."…”
Section: Prediction Of the Function Of Microbiotamentioning
confidence: 99%
“…The availability of sequence databases is very useful for a better understanding of host-pathogen interactions 19 , feeding mechanisms 20 , development 21 , and defense pathways in phytophagous insects 22 . Additionally, a significant number of studies using transcriptomic-based approaches have focused on identifying genes involved in developmental processes, with expression profiles among different life stages reported in several insect species 21,23,24 . Recent studies have reported such gene expression analyses across different developmental stages in lepidopteran pests of global economic relevance 2426 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a significant number of studies using transcriptomic-based approaches have focused on identifying genes involved in developmental processes, with expression profiles among different life stages reported in several insect species 21,23,24 . Recent studies have reported such gene expression analyses across different developmental stages in lepidopteran pests of global economic relevance 2426 . Similarly, a number of such studies have been performed on coleopteran pests 21,27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…The COG database consists of proteins from complete genomes of bacteria, archaea and eukaryotes, and each categorized COG term represents an ancient conserved domain. 30 As shown in Fig. 8A, the results proved that COG terms of differential ora in small intestine (p < 0.05) were mainly contained "[F] Nucleotide transport and metabolism", "[G] Carbohydrate transport and metabolism" and "[J] Translation, ribosomal structure and biogenesis".…”
Section: Cog and Kegg Analysesmentioning
confidence: 82%